The Relationship Between Knowledge Level and Student Compliance in Performing Personal Protective Equipment Usage Procedures: A Study in the Department of Dental Health, Poltekkes Kemenkes Kupang - Baunsele, Novianti; Ramli, Fitri Idayani; Pay, Mery Novaria (Yayasan Ahmad Mansyur Nasirah, 2024)
Standard precautions play a crucial role in preventing infections among patients, healthcare workers, and practicing students. The use of personal protective equipment (PPE), such as gloves, masks, protective glasses, and protective clothing, helps prevent risks associated with needle-stick injuries, aerosol splashes, and water sprays. A preliminary study revealed that 70% of students do not comply with PPE usage, and 50% have inadequate knowledge regarding PPE. This study aims to analyze the relationship between students' knowledge levels and their compliance with PPE usage. Using an analytical observational design with a cross-sectional approach, the study involved 97 fifth-semester students undergoing practical training in the dental and oral healthcare laboratory from February to June 2024. The sample was selected using a total sampling technique, while data were collected through questionnaires, checklists, and interviews. Data analysis was performed using the Kendall Tau-b correlation test. The results showed that 52.6% of students had good knowledge of PPE, while 70.1% were categorized as compliant in its use. The Kendall Tau-b correlation test indicated a significant relationship between knowledge level and compliance with PPE usage (p = 0.027 < 0.05). In conclusion, higher knowledge levels about PPE are associated with greater compliance among students. Therefore, more intensive training and socialization efforts are needed to enhance students' adherence to PPE implementation.